Advances in taxation. Vol. 15 - Porcano, Thomas M. (Advances in taxation,, 2003)
Advances in Taxation publishes articles dealing with all aspects of taxation. Articles can address tax policy issues at the federal, state, local, or international level. The series primarily publishes empirical studies that address compliance, computer usage, education, legal, planning, or policy issues. These studies generally involve interdisciplinary research that incorporates theories from accounting, economics, finance, psychology, and sociology.